Pengaruh Budaya Kesehatan dan Kesehatan Mental terhadap Prestasi Belajar Siswa Sekolah Dasar - Syahdat Al Afgani Mahmud Yunus; Taufik Zulfikar; Rahadian Malik (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the influence of health culture and mental health on the learning achievement of elementary school students. The background of this research is based on the importance of students’ physical and psychological conditions as factors that support optimal academic success. Students with good health conditions tend to be better able to participate effectively in the learning process. This study uses a quantitative approach with a cross-sectional design. The sample consists of all fourth, fifth, and sixth grade students at SD Negeri Margaluyu 1 and 2 in Cianjur Regency, totaling 184 students, using a saturated sampling technique in which the entire population is included as respondents. Data were collected through questionnaires that had been tested for validity and reliability to ensure the accuracy of the research instruments. Data analysis was conducted using multiple linear regression to determine the relationships among variables. The results show that health culture has a significant effect on students’ learning achievement, while mental health does not have a partial effect on learning achievement. However, simultaneously, health culture and mental health have a significant influence on students’ learning achievement. This study emphasizes the importance of strengthening healthy lifestyle culture and paying attention to mental health as part of strategies to improve learning achievement in elementary schools sustainably.